2015
DOI: 10.3171/2014.11.jns131888
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of direct magnetic resonance imaging-guided placement of drug infusion cannulae

Abstract: An intraoperative MRI (iMRI)–compatible system has been developed for direct placement of convection-enhanced delivery (CED) cannulae using real-time imaging. To establish the precision and feasibility of this technology, the authors analyzed findings in patients who underwent direct iMRI CED cannula placement. Three consecutive patients underwent iMRI-guided placement of CED infusion cannulae (6 cannulae) for treatment of diffuse intrinsic brainstem glioma (2 patients) or Parkinson’s disease (1 patient). Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Randomized trials of CED therapy have not yet shown so far survival advantages as compared with standard of care. An intraoperative magnetic resonance imaging (MRI)-compatible system has been developed for direct placement of CED cannulae using real-time imaging ( Figure 1A) (15). In particular, catheter design and placement-in are critical components of any CED protocol (34).…”
Section: Convection-enhanced Deliverymentioning
confidence: 99%
See 3 more Smart Citations
“…Randomized trials of CED therapy have not yet shown so far survival advantages as compared with standard of care. An intraoperative magnetic resonance imaging (MRI)-compatible system has been developed for direct placement of CED cannulae using real-time imaging ( Figure 1A) (15). In particular, catheter design and placement-in are critical components of any CED protocol (34).…”
Section: Convection-enhanced Deliverymentioning
confidence: 99%
“…However, early studies may have been limited by "first generation" delivery techniques and recently reported improvements may potentially allow for better outcomes (26). Coupled with computational methods allowing a better determination of the biodistribution of the infusate (34), the above cannula insertion procedures may improve the thoroughness of CED for HGG treatment (15). An intraoperative magnetic resonance imaging (MRI)-compatible system has been developed for direct placement of CED cannulae using real-time imaging ( Figure 1A) (15).…”
Section: Convection-enhanced Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…3,4,8 To overcome these limitations, technology has been developed that now permits the integration of intraoperative MRI (iMRI) with frameless stereotaxy. The resolution and real-time feedback of this iMRI technology has been demonstrated in phantom experiments, 12,18 nonhuman primate studies, 16,17 drug infusion cannula placement, 2 and placement of deep brain stimulator leads. 9,11,20,21 Application of this technology to stereotactic brain biopsy could eliminate misdiagnosis secondary to faulty targeting, provide realtime adaptability for needle trajectory, confirm accurate biopsy cannula position, and provide immediate imaging of complications.…”
mentioning
confidence: 99%